Organizational strategies in the operating room during COVID 19 pandemic: An integrative review - Maciel Ferreira, José Erivelton de Souza; Rocha de Oliveira, Lídia; Galvão Pereira, Karoline; Marques Frota, Natasha; Frota Cavalcante, Tahissa; Santos Monte, Alana; Lopes Chaves, Anne Fayma (Revista Cuidarte, 2022)
Introduction: Health systems were challenged to develop organizational strategies for the delivery of surgical care. Objective: to present the strategies of health services with regard to surgical care practices in times of the COVID-19 pandemic. Materials and methods: An integrative review was conducted following six stages; the search for articles was performed using the Virtual Health Library, SciELO, PubMed, and ScienceDirect. The science descriptors adopted were “Surgicenters” and “Coronavirus Infections,” according to the DeCS-MeSH terms system. We selected 60 articles from 405 studies found. Results: The main strategies used by the health services were to suspend and postpone elective surgeries during waves of disease transmission and careful screening of patients with COVID-19 before and after surgery. Discussion: The suspension and postponement of elective surgeries should be carefully evaluated by the health team, individually for each patient since non-urgentclinical situations may worsen over time, increasing the chances of morbidity and mortality in these patients. Conclusion: screening patients and health professionals for COVID-19, according to the reality of surgical units, centers or outpatient clinics, is an important strategy to avoid contamination of these subjects. The suspension and postponement of elective surgeries, during the waves of contagion by COVID-19, is recommended to increase the capacity of beds available for critically ill patients hospitalized for this disease. This recommendation also helps in the reassignment of professionals in this sector to the units with the highest demand for health care.How to cite this article: Ferreira José Erivelton de Souza Maciel, Oliveira Lídia Rocha de, Pereira Karoline Galvão, Frota Natasha Marques, Cavalcante Tahissa Frota, Monte Alana Santos, Chaves Anne Fayma Lopes. Estratégias organizacionais no centro cirúrgico diante da pandemia de COVID 19: uma revisão integrativa. Revista Cuidarte. 2022;13(2):e2323. http://dx.doi.org/10.15649/ cuidarte.2323
Keywords: Coronavirus Infections; Surgicenters; Surgical Procedures, Operative